Antibacterial and anti‐inflammatory effects of genistein in Staphylococcus aureus induced osteomyelitis in rats. Issue 4 (2nd February 2023) - Guo, Xinyi
Abstract: Methicillin‐resistant Staphylococcus aureus (MRSA) is a highly infectious Gram‐positive pathogen known to cause severe diseases such as endocarditis, food poisoning, pneumonia, osteomyelitis, and septicemia. MRSA is a major public health issue. Among these, osteomyelitis is inflammation of the bone caused by the invasion of the bacterial pathogen in the bones. Its prominent symptoms include fever, pain, and redness of bones. In the case of children, it affects the long bones of arms and legs, whereas in the case of adults it affects the hip, feet, and spine. Bacterial osteomyelitis can trigger pathological remodeling of bones and hence causes substantial morbidity and mortality. The present study aims to evaluate the isoflavone genistein's (5, 7‐dihydroxy‐3‐(4‐hydroxyphenyl)−4H‐1‐benzopyran‐4‐one, 4′, 5, 7 trihydroxyisoflavone) antimicrobial and anti‐inflammatory effects against osteomyelitis induced by MRSA in male Wistar rats. Classification of the animals was into the following: sham (Group I), osteomyelitis (Group II, control), genistein (25 mg/kg body weight, Group III), and genistein (50 mg/kg body weight, Group IV). The rats did not receive any treatment for 4 weeks after bacterial inoculation. Genistein was then administered twice daily for 2 weeks. Bacterial growth, mean body weight bone infection status, and side effects of genistein treatment were assessed. Furthermore, lipid peroxidation, superoxide dismutase, glutathione (GSH) peroxidase, catalase, reduced GSH, tumor necrosis factor‐α (TNF‐α), and interleukin (IL)‐6 were also determined. Two days after treatment, it was found that genistein significantly suppressed bacterial growth and reduced serum pro‐inflammatory cytokines TNF‐α and IL‐6. Therefore, the study suggests that genistein could be a promising lead against MRSA‐induced osteomyelitis.